2000
DOI: 10.1007/s000110050566
|View full text |Cite
|
Sign up to set email alerts
|

Augmented prostaglandin E 2 generation resulting from increased activities of cytosolic and secretory phospholipase A 2 and induction of cyclooxygenase-2 in interleukin-1 β -stimulated rat calvarial cells during the mineralizing phase

Abstract: Augmented PGE2 production by mineralizing osteoblasts after IL-1beta treatment, and the involvement of IL-1beta-induced cPLA2, sPLA2, COX-2 and PGE synthase activities in this phenomenon were demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…These data are in agreement with IL-1␤-induced activation of MAPKs (Hungness et al, 2002;Parker et al, 2002) and cPLA 2 (Beasley, 1999;Higashi et al, 2000) in variety of cells. Our data suggest that H 2 O 2 production induced by shortperiod incubation with IL-1␤ does not depend on activation of NF-B, even though NF-B may be activated by IL-1␤ (Janssen- Heininger et al, 2000;Ganster et al, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…These data are in agreement with IL-1␤-induced activation of MAPKs (Hungness et al, 2002;Parker et al, 2002) and cPLA 2 (Beasley, 1999;Higashi et al, 2000) in variety of cells. Our data suggest that H 2 O 2 production induced by shortperiod incubation with IL-1␤ does not depend on activation of NF-B, even though NF-B may be activated by IL-1␤ (Janssen- Heininger et al, 2000;Ganster et al, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…Additional studies in the authors' lab have pursued this line of reasoning and further described the role of phospholipase A 2 in the response of osteoblasts to Ti surface roughness and 1,25(OH) 2 D 3 , 44,45 while others have reported on the involvement of phospholipase A 2 and COX-2 in augmenting PGE 2 production during mineralization of rat calvarial cells. 46 Studies have shown that MG63 cells cultured on titanium disks of increasing roughness, similar to those used in the current study, produce increased amounts of PGE 2 . 18 On smooth Ti, the cultures were found to produce 50 pg/mL (¼ 0.7 nM) of PGE 2 , while those on rough Ti produced 160 pg/mL (¼ 4.5 nM).…”
Section: Discussionmentioning
confidence: 81%
“…VOL. 21,2001 PLIP INTERACTS WITH cPLA 2 AND POTENTIATES APOPTOSIScPLA 2 expression has also been closely linked to PGE 2 generation (2,11,32,49,53), which has been shown to have both pro- (17,49,60) and anti-(58) apoptotic effects. We compared PGE 2 generation in Ad-PLIP-infected cPLA 2 ϩ/ϩ and cPLA 2 Ϫ/Ϫ mesangial cells incubated in serum-free medium for 48 h. PLIP expression markedly increases PGE 2 production in cPLA 2 ϩ/ϩ but not cPLA 2 Ϫ/Ϫ cells (Fig.…”
Section: Resultsmentioning
confidence: 99%